Tinjauan Yuridis Terhadap Tindak Pidana Perdagangan Orang Oleh Penyedia Jasa Pekerja Seks Komersial (Studi Putusan Nomor 741/Pid.Sus/2016/PN. Mdn) - Andreas Teguhta Kaban; Aulia Rosa Nasution; Ridho Mubarak (JUNCTO: Jurnal Ilmiah Hukum, 2020)
The crime of trafficking in persons (human trafficking) is a very complex crime so it is difficult to eradicate. However, attention to trafficking in persons is more focused on women as vulnerable groups in this discussion (women trafficking). The purpose of this study is to see more clearly that there is still a link between the crime of commercial sex worker service providers with the crime of trafficking in persons. The method of approach that the authors take in this research is descriptive qualitative. The underlying factors are economic, family, religious, lack of awareness, the desire to get rich quickly. The legal provisions in Law Number 21 of 2007 concerning the Criminal Act of Trafficking in Persons have been supplemented with implementing regulations, namely Government Regulation Number 9 of 2008 concerning Procedures and Mechanisms for Integrated Services for Witnesses and / or Victims of Trafficking in People in Article 1 paragraph 1 and Presidential Regulation No. 69/2008 concerning the Prevention and Handling of Criminal Acts of Trafficking in Persons Article 4. Legal Analysis that the Defendant is proven guilty of committing a crime "intentionally as a livelihood or habit of committing or facilitating obscene acts with others" and the Defendant has become a pimp by providing women who are trafficked for sexual services so that the Defendant benefits from these actions.